Functional Magnetic Resonance Imaging Reveals Early Connectivity Changes in the Auditory and Vestibular Cortices in Idiopathic Sudden Sensorineural Hearing Loss With Vertigo: A Pilot Study - Wang, Qiuxia; Chen, Qingguo; Liu, Ping; Zhang, Jing; Zhou, Liangqiang; Peng, Liyan (Frontiers in Human Neuroscience, 2021)
The underlying pathophysiology of idiopathic sudden sensorineural hearing loss (ISSNHL) with vertigo has yet to be identified. The aim of the current study was to elucidate (1) whether there were functional changes of the intrinsic brain activity in the auditory and vestibular cortices of the ISSNHL patients with vertigo using resting-state functional magnetic resonance imaging (rs-fMRI) and (2) whether the connectivity alterations were related to the clinical performance associated with ISSNHL with vertigo. Twelve ISSNHL patients with vertigo, eleven ISSNHL patients without vertigo and eleven healthy subjects were enrolled in this study. Rs-fMRI data of auditory and vestibular cortices was extracted and regional homogeneity (ReHo) and seed-based functional connectivity (FC) were evaluated; the chi-square test, the ANOVA and the Bonferroni multiple comparison tests were performed. Significantly decreased ReHo in the ipsilateral auditory cortex, as well as increased FC between the inferior parietal gyrus and the auditory cortex were found in the ISSNHL with vertigo groups. These findings contribute to a characterization of early plastic changes in ISSNHL patients with vertigo and cultivate new insights for the etiology research.